2000
DOI: 10.1063/1.1312854
|View full text |Cite
|
Sign up to set email alerts
|

Direct x-ray synchrotron imaging of strains at 180° domain walls in congruent LiNbO3 and LiTaO3 crystals

Abstract: Determination of three-dimensional orientations of ferroelectric single crystals by an improved rotating orientation x-ray diffraction method Rev. Sci. Instrum. 80, 085106 (2009); 10.1063/1.3204781 X-ray diffraction imaging of strain fields in a domain-inverted LiTaO 3 crystal J. Appl. Phys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 14 publications
4
26
1
Order By: Relevance
“…14 However, it is consistent with the results of x-ray synchrotron imaging of domains in lithium niobate and lithium tantalate crystals, which showed significant broadening of the 180°domain walls as well as with theoretical estimations of the wall width in these materials based on experimentally measured coercive fields. 15,16 Note that situation may be different in ultrathin crystals. 2 Figure 2 shows the domain radius as a function of the pulse magnitude for various pulse durations.…”
mentioning
confidence: 99%
“…14 However, it is consistent with the results of x-ray synchrotron imaging of domains in lithium niobate and lithium tantalate crystals, which showed significant broadening of the 180°domain walls as well as with theoretical estimations of the wall width in these materials based on experimentally measured coercive fields. 15,16 Note that situation may be different in ultrathin crystals. 2 Figure 2 shows the domain radius as a function of the pulse magnitude for various pulse durations.…”
mentioning
confidence: 99%
“…16 dispersion of K for higher Bi-content specimens. Maxima in 0.12 the room temperature dielectric peaks were observed as a 800.…”
Section: Resultsmentioning
confidence: 99%
“…In stoichiometric crystals strain and birefringence tend to disappear; thus these effects and the large wall width are clearly connected with lattice defects. Kim et al [16] used X-ray synchrotron diffraction imaging to study strain components when crossing the wall and found that they represent wall thickness of several pLm in both congruent LiNbO 3 and LiTaO 3 .…”
Section: Domain Wall Thicknessmentioning
confidence: 99%
“…These corrugations also provide satellites with spacings of 1=Ã. Surface domain-wall thicknesses for LN and KTP of w = 0.15-15 mm (Yang & Mohideen, 1998;Kim et al, 2000;Wittborn et al, 2002) and 20-80 nm (Wittborn et al, 2002), respectively, have also been reported. The Malis-Gleiter model of a ferroelectric domain wall (Malis & Gleiter, 1976) supposes that the electric dipole rotates from P S to ÀP S over the domain-wall width, w, and so the structure factor in the region of this rotation, F rot , is assumed to be less than F H or F H , in the surrounding domains.…”
Section: Simulationmentioning
confidence: 97%
“…This anisotropy is explained in terms of the Miller-Weinreich model (Miller & Weinreich, 1960). X-ray topography, which can investigate the surface and bulk, has been used to study PDI LiTaO 3 and estimate domain-wall widths of a crystalline sample in the bulk (Kim et al, 2000). Results from the literature are summarized in Tables 1 and 2.…”
Section: Introductionmentioning
confidence: 99%